White king - Gómez-Jurado, Juan (Gómez-Jurado, Juan. Antonia Scott, 2025)
"Antonia Scott has an unusually gifted forensic mind, whose ability to reconstruct crimes and solve baffling murders is legendary. She's the lynchpin of a top-secret project, Red Queen, created to work across borders and behind the scenes to solve the most devious and dangerous crimes, those that are beyond the skills of the regular police forces. But the Red Queen project is under attack on all fronts. Across Europe, its agents are murdering each other and cases from the past, long believed resolved, are rearing their deadly heads again. At the center of it is the mysterious Mr. White, who has been weaving a web around Antonia for a very long time. He is as smart and capable as her but, unlike her, he's a psychotic killer who has isolated Antonia Scott. Jon Gutierrez, Antonia's protector and the only person she trusts, has been kidnapped. Antonia's husband has been killed and her remaining family is in hiding. With Jon's life at stake, Mr. White gives her a seemingly innocuous challenge: solve three crimes and bring the perpetrators to justice. The only way to keep Jon alive is to play Mr. White's game, but can even Antonia win a game when she can only see part of the board?"--